PENGARUH PERSEPSI KUALITAS DAN PERLUASAN LINI TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA KONSUMEN TEH BOTOL SOSRO KEMASAN PET 450ML VARIAN 3 RASA DI MINI MARKET SURABAYA SELATAN) - SURIA YULINDA, IKA (Jurnal Ilmu Manajemen (JIM), 2016)
The purpose of this researh is to analyze and discuss about the influence of the perceived quality and the line extenison on purchasing decisions of Teh Botol Sosro PET packaging 450ml with three variants flavor. This research using non-probability sampling with incidental sampling as sampling category. This research take 210 people as a respondents of the sample object. The respondents of this research are people who have ever bought and consumed Teh Botol Sosro PET packaging 450ml with three variants flavor by the minimal age of 18 years old. The scale of this reseacrh using Likert scale, with questionnaire counting as measuring tool. Analysis of data using multiple linear regression model. The result of this research showed that perceived quality has positively affect on the purchase decisions, and line extension has positive influence on the purchase decisions. Keywords: perceived quality, line extension, and purchase decisions.